1997
DOI: 10.1016/s0092-8674(00)80341-4
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Transport by Distinct Populations of COPI-Coated Vesicles

Abstract: Electron microscope immunocytochemistry reveals that both anterograde-directed (proinsulin and VSV G protein) and retrograde-directed (the KDEL receptor) cargo are present in COPI-coated vesicles budding from every level of the Golgi stack in whole cells; however, they comprise two distinct populations that together can account for at least 80% of the vesicles budding from Golgi cisternae. Segregation of anterograde- from retrograde-directed cargo into distinct sets of COPI-coated vesicles is faithfully reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
319
1
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(352 citation statements)
references
References 72 publications
23
319
1
9
Order By: Relevance
“…To distinguish between these possibilities, two experiments were performed. First, we tested whether a soluble resident of the ER lumen (BiP), a protein actively retrieved from the Golgi by the KDEL receptor pathway (Bole et al, 1986;Lewis and Pelham, 1992;Orci et al, 1997), is inappropriately secreted in hSac1-depleted cell populations. This is expected if hSac1 is required for formation of COP1 vesicles that help retrieve BiP.…”
Section: Functional Distinction Between Mammalian Sac1 and Arf Depletionmentioning
confidence: 99%
“…To distinguish between these possibilities, two experiments were performed. First, we tested whether a soluble resident of the ER lumen (BiP), a protein actively retrieved from the Golgi by the KDEL receptor pathway (Bole et al, 1986;Lewis and Pelham, 1992;Orci et al, 1997), is inappropriately secreted in hSac1-depleted cell populations. This is expected if hSac1 is required for formation of COP1 vesicles that help retrieve BiP.…”
Section: Functional Distinction Between Mammalian Sac1 and Arf Depletionmentioning
confidence: 99%
“…Additionally, the COP I coat functions in retrograde transport and perhaps also in anterograde transport, within the Golgi complex (Orci et al, 1997;Pelham and Rothman, 2000). The minimal machinery for the budding of COP I-coated vesicles consists of coatomer, a stable cytosolic complex comprising seven equimolar subunits, ␣-, ␤-, ␤Ј-, ␥-, ␦-, ⑀-, and -COP, and the small GTPase ARF in its GTP-bound form (Rothman and Wieland, 1996;Spang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1989; Orci et al. 1997). Genome‐wide association studies revealed that one mutation in Golgb1 Y1212C (rs3732410) appeared to have a dominant effect: the overall significance of this variant with a reduced risk of ischemic stroke in all sickle cell anemia (SCA) patients with stroke against control SCA patients (OR = 0.27; 95% CI = 0.14–0.52) (Katayama et al.…”
Section: Discussionmentioning
confidence: 99%